Effect of Poultry Manure Rates and Days after Anthesis on the Fruit Quality of Okra (Abelmoschus esculentus (L.) Moench) - Emeghara, Ursulla Ukamaka; Emmanuel, Charles Moses; Alabi, Olugbena Omotayo (Nepalese Journal of Agricultural Sciences, 2025)
The cultivation of okra (A. esculentus) is crucial for sustaining food security and meeting nutritional demands, yet optimizing fruit quality remains a challenge. This research aimed to determine the effect of poultry manure rates and days after anthesis on quality of okra fruits. The experiment was carried out at the Crop section of the Teaching and Research farm of Ibrahim Badamasi Babangida University, Lapai, Niger State, Nigeria. The experiment was laid in a 3×3 factorial design consisting of two factors namely poultry manure rates (0, 7.5 and 12.5t/ha) and days after anthesis (7, 14, and 21 days) in a Randomized Complete Block Design (RCBD) and replicated three times. The plot area was 6m2 with alley way of 1m between blocks and plots. The poultry manure was incorporated to the soil two weeks before planting and Okra seed were sown at a spacing of 50cm x 75cm in intra-row and inter-row spacing respectively. Data collected include: number of flowers/plots, number of fruits/plots, fruit length, fruit girth and the quality evaluation of okra fruits were evaluated. The result of the experiment revealed that the moisture content, dry matter, ash content, crude protein, carbohydrates and energy value of okra fruits were not significantly influenced by different rates of poultry manure and days after anthesis. However, significant differences were observed in the crude fat and crude fibre as application of 0t/ha of poultry manure produced significantly higher crude fat while 21 days after anthesis produced higher crude fibre.